Dengue infection as a potential trigger of an imported Plasmodium ovale malaria relapse or a long incubation period in a non-endemic malaria region. (March 2016) - Lupi, Otília; Ridolfi, Felipe; da Silva, Sidnei; Zanini, Graziela Maria; Lavigne, Aline; Nogueira, Rita Maria Ribeiro; Cruz, Maria de Fátima Ferreira da; Daniel-Ribeiro, Cláudio Tadeu; Brasil, Patrícia
Highlights: This is the first case report of concurrent dengue and Plasmodium ovale infections. Dengue fever (DF) seems to be able to trigger an ovale malaria relapse or a patent ovale malaria. DF, as a co-morbidity for malaria, could impact the fluid electrolyte management. Summary: Objectives: To report that dengue fever (DF) could have triggered Plasmodium ovale wallikeri malaria. Methods: A retrospective case report of P. ovale malaria and DF in a single patient in Rio de Janeiro, Brazil, who had lived in Angola, is presented. Results: On the second week of illness, the patient was referred to our research service. As symptoms had persisted up to day 14, malaria was also considered, based on the patient's long-standing epidemiological history. On day 16 of illness, a thick blood smear was positive for P. ovale (3480 parasites/mm 3 ), PCR for malaria was positive for P. ovale wallikeri, and the kinetics of dengue virus (DENV) antibodies suggested a recent primary dengue infection. Conclusions: Concurrent infections of DENV and malaria have rarely been reported; the actual impact of these sequential or simultaneous infections remains unknown. Therefore, DF must be considered as a potential co-morbidity for malaria, because of its influence on fluid electrolyte management. The case presented showed consistent temporal, clinical, and laboratory evidence that the relapse or the long incubation period of P. ovale malaria may have been triggered by a recent DF episode. To the authors' knowledge, this is the first report of DENV and P. ovale co-infection.